Taxonomy and distribution of irregular echinoids (Echinoidea: Irregularia) from Sri Lanka - Arachchige, Gayashan M.; Jayakody, Sevvandi; Mooi, Rich; Kroh, Andreas (Zootaxa, 2019)
The earliest information on Sri Lankan echinoid species belonging to the Irregularia dates back to Alexander Agassiz (1872). However, the current knowledge of diversity and distribution of irregular echinoids from Sri Lanka (formerly Ceylon) remains sparse. In addition, there are no recent taxonomic studies or biodiversity surveys for irregular echinoids, and no illustrated field-guides or reference collections are available specifically for Sri Lanka. To address these gaps, left open for more than 100 years since the work of Clark (1915), this study was conducted as an island-wide systematic sampling survey. Over 200 echinoid specimens were collected from 24 localities in Sri Lankan coastal waters by snorkelling and SCUBA diving down to 33 m depth. The collected specimens were identified using existing keys and authenticated with specimens available at the Natural History Museum in Vienna, Austria. The present study records 22 irregular echinoid species belonging to 15 genera and nine families in four orders. Among the identified irregular echinoids, six species, Echinocyamus megapetalus H.L. Clark, 1914, Fibularia ovulum Lamarck, 1816, Fibulariella angulipora Mortensen, 1948, Echinodiscus cf. truncatus L. Agassiz, 1841, Peronella oblonga Mortensen, 1948 and Brissus cf. agassizii Döderlein, 1885, are new records for Sri Lanka. Four unidentified, possibly new species belonging to the genera Fibularia, Jacksonaster and Metalia are reported, but kept in open nomenclature until more material becomes available. At present, the diversity of irregular echinoids from Sri Lanka now stands at 37 species representing 11 families in four orders. A dichotomous key is presented for all Sri Lankan irregular echinoids.